FUNGSI PELAKU DALAM KALIMAT PASIF BAHASA INDONESIA - Saidi, Suher M. (Paramasastra: Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2016)
Function actors in Indonesian passive sentences often escape discussion books Indonesian syntax. The discussion focused on the function of more active voice. Treatment of the passive voice is restricted to the existence of an active sentence. In some syntactic outstanding books in general, functions of the perpetrators not be discussed in a clear and detailed. The average of these books use the concept of the subject (actor) in the active sentence becomes the object (the perpetrator) if subjected to a passivating process. The purpose of this study demonstrate the concept of correct function in accordance with the rules of syntax Indonesian. This study uses descriptive qualitative reviewed the literature to examine the function of the perpetrator based on syntactic theories, especially theories on the book Raw Indonesian Grammar as the main reference book. In addition, other books about the theory of syntax also be literature studies. The results of this study describes that concept of the function of the sentence in the passive voice. The results of this study were 1) the function of the actors in the passive voice can serve as complementary actors, title, and description, 2) the object never appears in the passive voice